Effect of fine aggregates on the strength and hydraulic properties of pervious concrete - Nazeer, Mudasir; Kapoor, Kanish; Singh, S. P. (Journal of Asian Concrete Federation, 2022)
In this study, the effect of inclusion of fine aggregates on the strength and hydraulic properties of pervious concrete have been investigated. A total of three mixes were casted using three different proportions of fine aggregates at a constant water to cement ratio and powder to aggregate ratio of 0.35 and 0.16 respectively. The partial inclusion of Natural Fine Aggregates (NFA) in place of Natural Coarse Aggregates (NCA) was done in the proportion of 0%, 10% and 20% respectively. The influence of NFA was investigated by performing workability, permeability and compressive strength at different curing periods. It was observed from the results that incorporation fine aggregates in pervious concrete up to 20% increases the compressive strength values significantly. A maximum increment of 17% in compressive strength was seen at 20% of NFA at 28 days of curing. Moreover, it was observed from the microstructure observations that a dense and layered calcium-silicate- hydrate (C-S-H) was seen for mix M20. It was further investigated from energy dispersive x-ray spectrometer that 50-60% of volume was occupied by C-S-H gel for mix M20.